Design of Monitoring and Control Devices for Bird Repellents in Rice Fields Based on IoT - Muhammad Irfan; Muhammad Nasir; Guntur Syahputra (Politeknik Negeri Lhokseumawe, 2026)
Technological developments are advancing rapidly every year, such as the technology developed in various aspects of life, one of them is the Internet of Things, one of which can be applied in agriculture. The role of IoT in agriculture: In general, farmers have problems with rice quality due to pests in rice fields, which is a serious problem, such as bird pests. This results in a decline in rice quality. In this study, the author came up with an idea to solve this problem by designing an IoT-based bird repellent system. The author also hopes that this research can help the community or farmers in repelling birds from rice fields in a way that can be controlled or monitored using an IoT application. This study uses the QoS method, which functions as a measurement of network performance. The results of network measurement using the QoS method showed an average throughput of 75 kbps, packet loss of 0.1%, and delay of 61 ms. Based on the testing, the rice pest repellent showed performance capable of detecting bird pests at the distances of 80 cm, and was also able to detect grasshoppers at a distances of 20 cm. On the other hand, this device was also able to detect humans at a distances of 500 cm. During operation, when bird pests are detected, the gearbox motor will move automatically, and the DC siren will activate automatically, indicating the presence of bird pests.